Dual role of proliferating cell nuclear antigen monoubiquitination in facilitating Fanconi anemia-mediated interstrand crosslink repair - Shah, Ronak; Aslam, Muhammad Assad; Spanjaard, Aldo; de Groot, Daniel; Zürcher, Lisa M; Altelaar, Maarten; Hoekman, Liesbeth; Pritchard, Colin E J; Pilzecker, Bas; van den Berk, Paul C M; Jacobs, Heinz (PNAS nexus, 2024)
Abstract The Fanconi anemia (FA) repair pathway governs repair of highly genotoxic DNA interstrand crosslinks (ICLs) and relies on translesion synthesis (TLS). TLS is facilitated by REV1 or site-specific monoubiquitination of proliferating cell nuclear antigen (PCNA) (PCNA-Ub) at lysine 164 (K164). A PcnaK164R/K164R but not Rev1−/− mutation renders mammals hypersensitive to ICLs. Besides the FA pathway, alternative pathways have been associated with ICL repair (1, 2), though the decision making between those remains elusive. To study the dependence and relevance of PCNA-Ub in FA repair, we intercrossed PcnaK164R/+; Fancg−/+ mice. A combined mutation (PcnaK164R/K164R; Fancg−/−) was found embryonically lethal. RNA-seq of primary double-mutant (DM) mouse embryonic fibroblasts (MEFs) revealed elevated levels of replication stress-induced checkpoints. To exclude stress-induced confounders, we utilized a Trp53 knock-down to obtain a model to study ICL repair in depth. Regarding ICL-induced cell toxicity, cell cycle arrest, and replication fork progression, single-mutant and DM MEFs were found equally sensitive, establishing PCNA-Ub to be critical for FA-ICL repair. Immunoprecipitation and spectrometry-based analysis revealed an unknown role of PCNA-Ub in excluding mismatch recognition complex MSH2/MSH6 from being recruited to ICLs. In conclusion, our results uncovered a dual function of PCNA-Ub in ICL repair, i.e. exclude MSH2/MSH6 recruitment to channel the ICL toward canonical FA repair, in addition to its established role in coordinating TLS opposite the unhooked ICL.